2004
DOI: 10.1200/jco.2004.11.123
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Deoxyribonucleic Acid As Prognostic Marker in Non–Small-Cell Lung Cancer Patients Undergoing Chemotherapy

Abstract: Our data demonstrate that quantification of plasma DNA is an accurate technique amenable to standardization, which might complement current methods for the prediction of patient survival. This approach might be considered for evaluation in large prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
228
4
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(263 citation statements)
references
References 20 publications
26
228
4
5
Order By: Relevance
“…Although the precise mechanism of DNA release into the blood remains uncertain, it probably derives from a combination of apoptosis, necrosis and active release from tumour cells [6]. Such cell-free DNA has shown promise for improving early clinical diagnosis, prognostication and disease monitoring in inaccessible tumour types, such as lung cancer [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise mechanism of DNA release into the blood remains uncertain, it probably derives from a combination of apoptosis, necrosis and active release from tumour cells [6]. Such cell-free DNA has shown promise for improving early clinical diagnosis, prognostication and disease monitoring in inaccessible tumour types, such as lung cancer [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…To date, many candidate markers have been reported in relation to the clinical outcome of HCC patients (Marrero and Lok, 2004;Kuramitsu and Nakamura, 2006). In addition to these biomarkers, circulating cell-free DNA (cfDNA) has attracted a great deal of attention as an easy-to-use tool for evaluation of the malignant potential of cancer (Gautschi et al, 2004;Umetani et al, 2006). By means of real-time polymerase chain reaction (PCR) assay, we found that cfDNA levels were significantly higher in sera from patients with HCV-related HCC than in sera from HCV carriers without known HCC (Iizuka et al, 2006a).…”
mentioning
confidence: 99%
“…Qualitative alterations in circulating DNA, such as microsatellite alterations [10], oncogene mutations [11], mitochondrial DNA, tumour-speciWc methylated DNA [12] and viral DNA [13], have been found in patients with diVerent types of cancer. Quantitative alterations of circulating cfDNA have also been observed in several cancers, such as prostate cancer [14], lung cancer [15], pancreatic cancer [16], leukaemia and lymphoma [17]. High levels of circulating cfDNA were correlated with tumour metastasis, response to therapy and recurrence [15,18].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative alterations of circulating cfDNA have also been observed in several cancers, such as prostate cancer [14], lung cancer [15], pancreatic cancer [16], leukaemia and lymphoma [17]. High levels of circulating cfDNA were correlated with tumour metastasis, response to therapy and recurrence [15,18].…”
Section: Introductionmentioning
confidence: 99%